The design of carbon monoxide gas control systems in rooms based on IoT - Jauhari, Mohammad Raafi; Eliza, Fivia; Candra, Oriza; Mukhaiyar, Riki (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
The increasing use of air-conditioned rooms in public entertainment venues but allowing visitors to smoke indoors makes some visitors feel uncomfortable. This final project aims to be able to design a carbon monoxide gas control device and carbon monoxide gas monitoring using IoT technology. The methodology for making this tool involves literature study methods in national journals and internet searches regarding projects that have been made before. Then identify problems in the field so that improvements can be made in tool design. In this tool, air content readings use the MQ-135 sensor to detect gas levels. Control uses the Ardiono Uno microcontroller as the data processing center, the ESP 8266 nodeMCU as the data sender to the application. From several experiments it was concluded that the tool operated as expected. It can be seen from the experimental data that the MQ-135 sensor works accurately in detecting the air quality levels in the room. It starts when the sensor detects air levels and then the reading results become input to start activating the relay for on/off the exhaust fan and also perfume, which will be active to neutralize the air in the room. The buzzer will activate when the reading value reaches the programmed gas level. The sensor reading value that is read will then appear on the LCD and also on the Blynk application.